Striking a balance : environment and natural resources policy in the Nixon-Ford years - Whitaker, John C. (Washington : American Enterprise Institute for Public Policy Research, 1976)
author served at the White House and the Department of Interior to help lay out the legislative and administrative strategies for correcting the environmental abuses and to chart a natural resources development policy with environmental safeguards. The book focuses on the policy options available, explains why the decisions were made the way they were, and sketches the political realities that sometimes limited the available courses of action. The dozen chapters are Conservation/Environment: Theodore Roosevelt to Richard Nixon; The Beginning (The President's Environmental Message Task Force and The President's Environmental Message to Congress); New Federal Institutions for Energy and Environment; Clean Water--How Soon, How Clean, How Costly; Clean Air--Technology or Not; Solid Waste--Will the Free Market Solve the Problem; Pesticides, Predator Control, and Toxic Substances; the Use of Land; The Legacy of Parks; Modernizing Energy and Mineral--Leasing Policy on the Public Lands; Offshore Oil, Superports, and the Environment; and Emerging Problems.
Includes bibliographical references and index.
aia 14/05/2018
Loans
Keywords: Environmental policy..; United States